ANALISIS LAPORAN KEUANGAN BERDASAR PSAK NO. 27 AKUNTANSI PERKOPERASIAN PADA KOPERASI WANITA AL BAROKAH KAMPUNG MERANCANG ILIR (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2019)
The aim of this research was to find out whether the Al Barokah Women's Cooperative in Kampong Merancang Ilir Gunung Tabur District had implemented PSAK No. 27 Accounting for Cooperatives for the presentation of cooperative financial statements. The analytical tool used in this study is PSAK No. 27 (Revised 1998) Cooperative Accounting, in PSAK No. 27 stated that the Cooperative Financial Report consists of Balance Sheet, Business Result Calculation, Cash Flow Report, Member Economic Promotion Report and Notes to Financial Statements. From the research data on cooperatives, namely balance sheet and Business Result Calculation for the period of 2016 and 2015 and supporting data in this study, analysis has been carried out in the hypothesis testing of the financial statements using the comparative balance sheet, from the analysis carried out it is known that financial statements presented by cooperatives at the end of 2016 not in accordance with PSAK No. 27 because it only consists of Balance Sheet and Calculation of Business Results, while the cooperative does not make cash flow reports, member economic promotion reports and notes to financial statements. In presenting the balance sheet and calculating the results of the cooperative's operations there are also errors, especially in the case of writing the account name and grouping income and expenses in the Calculation of Business Results.